Memory impairment: an intermediate clinical syndrome symptom in HTLV-1-infected patients? - Maria Rita GASCON; Michel E HAZIOT; Tatiane ASSONE; Luiz Augusto M FONSECA; Jerusa SMID; Augusto César Penalva de OLIVEIRA; Jorge CASSEB (Arquivos de Neuro-Psiquiatria)
Background Although classical human T-cell lymphocyte virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis syndrome is the most frequent HTLV-1-associated neurological disorder, some “minor” neurological disorders can be seen in “asymptomatic” carriers. These disorders, including cognitive alterations already described in clinical cases and studies, may constitute an intermediate syndrome (IMS) between the asymptomatic state and myelopathy. The aim of this study was to investigate the presence of cognitive deficits in patients with HTLV-1 virus, who usually are diagnosed as asymptomatic. Methods A total of 54 HTLV-1-infected patients were evaluated, 35 asymptomatic and 19 with minor neurological alterations (evaluated by a neurologist); 25 HTLV-1-seronegative individuals served as controls. The instruments used were: Beck’s Depression Inventory, Lawton’s Daily Life Activity Scale, and a complete neuropsychological battery. The application of these evaluation instruments was performed blindly, with the evaluator neuropsychologist not knowing the clinical condition of the patient. Results Most of the participants in this cohort, including seronegative controls, were female (n = 57, 72.21%), their mean age was 52.34 years (SD = 14.29) and their average schooling was 9.70 years (SD = 4.11). Discussion Participants classified with IMS had lower gross scores when compared with both the patients classified as asymptomatic and with the control group, and when tested for auditory episodic memory of immediate (p < 0.01), and late (p = 0.01), recall. Conclusion Patients with IMS presented with memory impairment when compared with asymptomatic patients and seronegative individuals; this is one of the symptoms that aids in the classification of the syndrome.